The impact of the paradigm shift in the pop industry business model - María Seguí Moreno (Culturas, 2015)
The present works is a synthesis of a final project for the Master’s Degree in Cultural Management. In the latest years, Internet has been the source of many changes in our society. The music industry has suffered a structural and irreversible change, which is reflected in the current vision of the business model held by music professionals. On the other hand, specialized magazines have become crucial as a filter for quality music, in a new scenario where musicians and consumers are in charge of establishing the guidelines to configure a new model.